Munasabah Fawatih Al-Suwar dengan Khawatin Al-Suwar Pada Al-Sab’u Al-Thiwal dalam Al-Qur’an (Studi Komparatif antara Tafsir al-Bahru al-Muhith Fi al-Tafsir dengan Tafsir Nazmu ad-Durar Fi Tanasubi al-Ayati Wa al-Suwar) - Habibur Rahman; Rusydi Rusydi; Syofyan Hadi (UNES Law Review, 2023)
This research began with the discovery that the Al-Qur'an has advantages and superiority over the holy books of other religions, this is because the Al-Qur'an was revealed in Arabic and the unique thing about Arabic is the language that has the most and most complete rules in the world, therefore opens up opportunities for writers to highlight the superiority of the verses of the Qur'an contained in Arabic, apart from being superior in terms of rules, the Qur'an is also superior in terms of harmony. and the correspondence between the verses at the beginning of the surah and the verses at the end of the surah, the verses at the beginning of the surah are known as fawatih al-suwar while the verses at the end of the surah are known as khawatim al-suwar. The study of looking for correlations between verses in the Qur'an is called the term munasabah in 'ulumul Qur'an, this munasabah study has a broad object, so in this research the author limits the research to al-sab'u al-thiwal (seven surahs which is long in the Koran). This research is of an ijti Prize nature, therefore it requires a comparison between two tafsir books which both discuss the munasabah of verses in the Qur'an, the two books are the book Tafsir al-Bahru al-Muhith Fi al-Tafsir by Abu Hayyan al- Andalusy and the book Nazmu ad-Durar Fi Tanasubi al-Ayati Wa al-Suwar by al-Biqa'i. There has been research on the munasabah of this verse, but there has been no research on the munasabah of fawatih al-suwar and khawatim al-suwar which compares tafsir books with a lughawi style as the author did in this research. This research was carried out using a pure literature review. , using data analysis methods from various primary and secondary documents. The main primary data in this research took the book of tafsir al-Bahru al-Muhith Fi al-Tafsir by Abu Hayyan al-Andalusy and the book Nazmu ad-Durar Fi Tanasubi al-Ayati Wa al-Suwar by al-Biqa'I, while the data Secondary data is taken from other data which is considered related to the theme of munasabah between verses of the Koran. The results of this research show that there are similarities and differences in the interpretation of the two tafsir books. The similarities between the two interpreters convey the same interpretation between the verses at the end of the previous surah and the verses at the beginning of the following surah, this is found in three places, and the differences are found in four places, from the results of comparing these two tafsir books, conclusions can be drawn that in looking for the munasabah between fawatih al-suwar and khawatim al-suwar in al-sab'u al-thiwal, the interpretation of al-Bahru al-Muhith is superior, because this commentary explains the munasabah between verses complete with the redaction of the verses that are interpreted and explains in detail lughawi rules contained in each verse.